Structured object-oriented formal language and method : 8th International Workshop, SOFL+MSVL 2018, Gold Coast, QLD, Australia, November 16, 2018, Revised selected papers /: 8th International Workshop, SOFL+MSVL 2018, Gold Coast, QLD, Australia, November 16, 2018, Revised selected papers. (2019) - Unknown
No abstract available